Market driven network neutrality and the fallacies of internet traffic quality regulation - Günter Knieps (International Telecommunications Society (ITS), 2011)
In the U.S. paying for priority arrangements between Internet access service providers and Internet application providers to favor some traffic over other traffic is considered unreasonable discrimination. In Europe the focus is on minimum traffic quality requirements. It can be shown that neither market power nor universal service arguments can justify traffic quality regulation. In particular, heterogeneous demand for traffic quality for delay sensitive versus delay insensitive applications requires traffic quality differentiation, priority pricing and evolutionary development of minimal traffic qualities.
Keywords: 330